2018
DOI: 10.3390/ijms19041185
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Extracellular ATP Desensitizes P2Y2 and P2X4 ATP Receptors Provoking Surfactant Impairment Ending in Ventilation-Induced Lung Injury

Abstract: Stretching the alveolar epithelial type I (AT I) cells controls the intercellular signaling for the exocytosis of surfactant by the AT II cells through the extracellular release of adenosine triphosphate (ATP) (purinergic signaling). Extracellular ATP is cleared by extracellular ATPases, maintaining its homeostasis and enabling the lung to adapt the exocytosis of surfactant to the demand. Vigorous deformation of the AT I cells by high mechanical power ventilation causes a massive release of extracellular ATP b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 106 publications
0
16
0
Order By: Relevance
“…In a recent study, Oluto et al reported that Streptococcus pneumoniae inhibits purinergic signaling by increased internalization of P2Y 2 receptors in alveolar epithelial cells [ 202 ]. This might result in reduced surfactant secretion and subsequent alveolar collapse [ 95 ].…”
Section: The Role Of P2 Receptors In Lung Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Oluto et al reported that Streptococcus pneumoniae inhibits purinergic signaling by increased internalization of P2Y 2 receptors in alveolar epithelial cells [ 202 ]. This might result in reduced surfactant secretion and subsequent alveolar collapse [ 95 ].…”
Section: The Role Of P2 Receptors In Lung Diseasementioning
confidence: 99%
“…An early study reported the involvement of P2Y receptors in the pathogenesis of VILI [ 204 ]. Hasan et al suggested that desensitization of P2Y 2 and P2X 4 receptors might contribute to the development of VILI [ 95 ]. Zheng et al presented results that in a two-hit mouse model of Pseudomonas aeruginosa pneumonia with high-pressure ventilation a specific P2Y 6 receptor antagonist partially attenuated inflammation and lung injury without interfering with the ability of the immune system to clear the bacteria [ 215 ].…”
Section: The Role Of P2 Receptors In Lung Diseasementioning
confidence: 99%
“…The reduced surfactant, in turn, collapsed the alveoli and exaggerated the increase in extracellular ATP. Subsequently, high extracellular ATP levels (>300 μM) exacerbated pulmonary edema and acute lung injury (83). Moreover, the paracrine regulation of surfactant production between AT I and AT II cells has been indicated as AT II cells secrete surfactant lipid in response to tonic stretch only in the presence of AT I cells.…”
Section: Purinergic Signaling In Acute Pulmonary Inflammationmentioning
confidence: 99%
“…Continuation of 30 cmH 2 O for 40 s gradually increases the proportion of open alveoli to 85%. In the expiratory phase, there is a delay of approximately 0.17 s before alveolar collapse commences and at 0.25 s an alveolus is collapsed [32]. Inspiration time in the ARDSNet protocol is too short to recruit the majority of alveoli and too long to prevent the alveoli from collapsing.…”
Section: Slow Recruitment With Airway Pressure Release Ventilationmentioning
confidence: 99%